Glacial rock flour increases photosynthesis and biomass of natural phytoplankton communities in subtropical surface waters: a potential means of action for marine CO2 removal - Bendtsen, Jørgen; Daugbjerg, Niels; Hansen, Jørgen L. S. (Frontiers in Marine Science, 2024)
Photosynthesis by phytoplankton reduces partial pressure of CO2 at the surface of the ocean and is therefore a potential means of action for a marine CO2 removal technology. Here we study how glacial rock flour may influence photosynthesis in the open ocean. Glacial rock flour is a fine-grained silicate mineral from the bedrock grinded by the Greenland Ice Sheet and enters the ocean via fjords and coastal waters. It is therefore a natural source of nutrients and trace metals to the ocean. It is easily accessible in large quantities and could be a suitable source for large-scale CO2 removal. The impact of suspended glacial rock flour was analyzed through 14 incubation experiments with natural phytoplankton communities sampled in the subtropical Atlantic. A significant increase in photosynthesis was found in 12 experiments where variable fluorescence Fv/Fm increased 12% and the average concentration of chlorophyll a increased significantly in comparison with control treatments during a 6-day period. Incubations with glacial rock flour showed a significant uptake of phosphorus whereas the average concentrations of silicate and dissolved inorganic nitrogen increased. Nutrient changes could be explained by increasing phytoplankton and microbial biomass, remineralisation of organic matter, and weathering (mobilization) of glacial rock flour. These short time experiments indicated that trace metals from glacial rock flour stimulated phytoplankton growth. Thus, glacial rock flour has the potential to increase photosynthesis and phytoplankton growth, and therefore may be a potential means of action for marine CO2 removal.